Sifat fisik, Organoleptic dan Aktivitas Antioksidan Sosis Ayam dengan Penambahan Ekstrak Daun Sirsak (Annona muricata l.) - Ismanto, Arif; Subaihah, Sitiani (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2020)
This study aims to determine the effect of adding soursop leaf extract (SLE) at level 0 (control), 2, 4, and 6% (the weight of SLE /the weight of the dough) on the physical, organoleptic and antioxidant qualities of chicken sausages. A Completely Randomized Design (CRD) was used in this study. Data analysis was performed using analysis of variance (ANOVA) and further tested using the Least Significant Difference Test (LSD). The results showed that differences in SLE levels did not significantly affect the physical quality of chicken sausages, but did change the color, aroma, texture, and taste. The color, smell, texture, and taste of chicken sausage with the addition of 6% SLE showed results that appeared to be greener, had a stronger soursop aroma, more elastic, and tasted more bitter than the other treatments (P <0.05). The lowest antioxidant activity was shown by SLE 0% in both the dough (39.78%) and cooked sausage (17.10%). The highest antioxidant activity was SLE 6%, with antioxidant activity of 57.63% in the dough and 37.43% in cooked sausages. The addition of chicken sausage does not affect physical quality but has a significant impact on the soursop leaf extract test on organoleptic color, aroma, texture, and taste. The best organoleptic quality is demonstrated at 4% SLE. The addition of soursop leaf extract level is accompanied by increased levels of antioxidants both in the dough and in cooked sausage.